Family Caregiver’s Perception and Comprehension toward Pressure Injury Prevention in Bedridden Patients after Discharge from Hospitals - Martono . (Journal of Global Pharma Technology, 2020)
Objectives: Perception and understanding of pressure injury care is an important basis for family caregivers in preventing pressure injuries in stroke paralysis patients.The aims of this study to assess the caregiver family's perceptions and comprehension in preventing pressure injury. Methods: The design of this study was cross sectional. The survey was conducted on 357 family caregivers in nursing homes, Indonesia. Potential participants were recruited from Family Caregiver who treated stroke paralysis patients who were bedridden after being discharged from the hospital in a nursing home. Predictor variables (independent) of this study consisted of perception and comprehension and the dependent variable of this study was prevention of pressure injuries. Data were collected using a questionnaire: The analysis used linear regression with a significance level of p ≤0.05. Results: Simultaneously, 36.1% of perception and comprehension explained the prevention of pressure injury as evidenced by the value R2 = 0.361; p (F test) = 0.049. Partially, 19.4% perception of the prevention of pressure injury prevention was proven to be p (t-test) =0.016; R2=19.4% and 12.2% comprehension explained the prevention of pressure injury as evidenced by the value of p (t-test) = 0.019; R2=12.2% with a confidence interval of 95%. Conclusion: Family caregiver’s comprehension of the prevention of pressure toward pressure injury prevention in bedridden patients after discharge from hospitals was low. Perceptions and comprehension factors of family caregivers contribute to the prevention of pressure injury in stroke paralysis patients who are bedridden.Keywords: Caregivers, Perception, Comprehension, Pressure injury.